Petrogenesis batuan vulkanik daerah tambang emas Lebong Tandai, Provinsi Bengkulu, berdasarkan karakter geokimianya - ZulkarnaIn, Iskandar (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no2.20081Lebong Tandai is a village in the Napal Putih Sub-regency, North Bengkulu Regency, that can be accessed only through the local people train called âmolekâ. The area is well known as a gold mine since the Dutch time. Volcanic rocks in the area belong to the Hulusimpang Formation that are dominated by andesitic rocks with small amount of dacite and basalt. They show an affinity as a transition between calc-alkaline and tholeiite. Its trace elements and REE patterns show that they are derived from âmagma oneâ, one of the two magma sources producing volcanic rocks in Bengkulu. âMagma oneâ is derived from a magma source with adakitic composition due to the most primitive sample among the âmagma oneâ samples. The Lebong Tandai magma activity has occurred since more than 30 million years ago in a back-arc side tectonical environment, and they were enriched on incompatible elements during an upper crust penetration. The occurrence of gold mineralization in this area indicates that the âmagma oneâ is a gold bearing mineralized magma in this region. It seems to be reasonable when it is corresponded with an investigation result reported from the Phillippine that adakitic rocks contain higher gold concentration than calc-alkaline rocks. This paper is written using a geochemical approach based on major elements, trace elements and rare earth elements (REE) that are plotted into general and specific classifications in a petrological discussion. Â